Understanding the impact of trunk and arm impairments on wheelchair rugby performance during competition - Mason, B. S.; Altmann, V. C.; Goosey-Tolfrey, V. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine the effect of trunk and arm impairments on physical and technical performance during wheelchair rugby (WR) competition. Methods: Thirty-one highly trained WR players grouped according to their trunk (no trunk [NT]; some trunk [T] function) and arm impairments (poor, moderate, and good arm function) participated in 5 WR matches. Players' physical (wheelchair mobility) and technical (ball handling) activities were analyzed using an indoor tracking system and video analysis, respectively. Results: Trunk impairment explained some of the variance in physical (10.6-23.5%) and technical (16.2-33.0%) performance. T covered more distance, had more possession, scored more goals, and received and made more passes yet spent less time at low speeds and performed fewer inbounds than NT (=.05). Arm impairment explained some of the variance in all physical (16.7-47.0%) and the majority of technical (13.1-53.3%) performance measures. Moderate and good arm function covered more distance, reached higher peak speeds, spent more time in higher speed zones, scored more goals, had more possession, and received and made more passes, with a higher percentage of 1-handed and long passes, than poor arm function. Good arm function also received more passes and made a higher percentage of 1-handed passes and defensive blocks than moderate arm function (P = .05). Conclusions: Arm impairment affects a greater number of physical and technical measures of performance specific to WR than trunk impairment during competition. Having active finger function (good arm function) yielded no further improvements in physical performance but positively influenced a small number of technical skills.